Advances in insect pest and disease monitoring and forecasting in horticulture - Vänninen, Irene (Burleigh Dodds Series in Agricultural Science, 2022)
Pest monitoring in horticulture is developing technologically to reduce time and labor needed for sampling and to produce more accurate pest predictions. New ways of detecting pests based on selective e-traps, e-noses, cameras and acoustic signatures are already in use or emerging. Remote sensing of pests requires the development of new economic injury levels and economic thresholds (ET). The relative importance of mechanistic and statistical models is changing due to AI-technologies and Big Data. The use of Big Data will force researchers to collect, use and value data differently than before. The incorporation of natural enemies in ETs will take place gradually and require researchers to acquire modeling skills. Research for advancing monitoring and forecasting also must include the socioeconomic factors that determine whether new technologies will be implemented by farmers. Developing trustworthy sampling plans and forecasting models,, and validating and implementing them in collaboration with stakeholders, remains important.